2016
DOI: 10.1212/wnl.0000000000002922
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk of Alzheimer disease is associated with early- and late-life processes

Abstract: Objective: To examine associations between aggregate genetic risk and Alzheimer disease (AD) markers in stages preceding the clinical symptoms of dementia using data from 2 large observational cohort studies. Methods:We computed polygenic risk scores (PGRS) using summary statistics from the International Genomics of Alzheimer's Project genome-wide association study of AD. Associations between PGRS and AD markers (cognitive decline, clinical progression, hippocampus volume, and b-amyloid) were assessed within o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
184
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(205 citation statements)
references
References 42 publications
19
184
2
Order By: Relevance
“…The minimal amount of statistically significant findings observed when assessing cognitive function is similar to the findings of two studies that concluded that a PRS based on all significant IGAP genes one including and one excluding APOE , was not associated with cognitive function in older non-demented individuals[34, 35]. Two other studies did find associations between cognitive function and an overall PRS using a subset of IGAP genes in general populations; however, removing APOE from the PRS eliminated the statistical significance[36, 37].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The minimal amount of statistically significant findings observed when assessing cognitive function is similar to the findings of two studies that concluded that a PRS based on all significant IGAP genes one including and one excluding APOE , was not associated with cognitive function in older non-demented individuals[34, 35]. Two other studies did find associations between cognitive function and an overall PRS using a subset of IGAP genes in general populations; however, removing APOE from the PRS eliminated the statistical significance[36, 37].…”
Section: Discussionsupporting
confidence: 78%
“…It will be crucial to modify these pathway-specific PRSs to reflect new findings in order to improve their predictive ability. One recent successful approach used a large number of the top IGAP SNPs (~16,000) to develop an overall PRS, potentially utilizing many other relevant genetic variants that did not meet statistical significance, and found that it was associated with cognitive function, Aβ deposition, hippocampal volume, and clinical progression[35]. A possible interesting expansion of this approach could be to develop pathway-specific PRSs using this large panel of SNPs and the pathways outlined by the IGAP pathway analysis[6].…”
Section: Discussionmentioning
confidence: 99%
“…Here, these prior observations are expanded on to show that these alterations are also present in early life process. Together, accumulating evidence now suggests that both common and rare variations that confer risk for AD may converge on pathophysiological mechanisms such as alterations in subcortical volumetry in early life [6,8]. Furthermore, there was a negative association between the TREM2 risk allele and volume of putamen.…”
Section: Discussionmentioning
confidence: 99%
“…Naj et al found that while APOE contributes to 3.9% of variation at age of onset, nine other IGAP SNPs together contribute to additional 1.1% variation [77]. The scores are also associated with clinical progression to AD and can predict progression from healthy controls [70•, 73, 75] or MCI [69] to AD. In addition, there is a relationship between higher score values and worsening behavioral and neuroimaging endophenotypes of the disease [73].…”
Section: Gwasmentioning
confidence: 99%